2002
DOI: 10.1002/1521-3749(200208)628:8<1917::aid-zaac1917>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral Coordination in the First Structurally Characterized Dichlorooxovanadium(V) Alkoxide

Abstract: Reaction of VOCl 3 with 2-phenoxyethanol in n-hexane in a 1:1 fashion gives dichlorooxo(2-phenoxyethanolato)vanadium(V). HCl elimination yields the orange vanadium(V) complex, which is the first structurally characterized dichlorooxovanadium(V) alkoxide. The structure analysis reveals an unexpected tetrahedral coordination around the vanadium atom in the monomeric Tetraedrische Koordination im ersten strukturell charakterisierten Dichlorooxovanadium(V)-alkoxidInhaltsübersicht. Die Reaktion von VOCl 3 mit 2-Phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…This class of vanadates has attracted extensive current research interests in modelling the coordination environment of vanadium-dependent haloperoxidases or nitrogenases [10]. In the context of developing vanadium catalysts for olefin polymerisation and oxidation our research group has reported a class of novel chloro vanadate complexes with aryloxyalkoxide [11] or alkoxyalkoxide ligands [12]. The aryloxyalkoxide derivative [VOCl 2 (OCH 2 CH 2 OPh)] is monomeric in the solid state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This class of vanadates has attracted extensive current research interests in modelling the coordination environment of vanadium-dependent haloperoxidases or nitrogenases [10]. In the context of developing vanadium catalysts for olefin polymerisation and oxidation our research group has reported a class of novel chloro vanadate complexes with aryloxyalkoxide [11] or alkoxyalkoxide ligands [12]. The aryloxyalkoxide derivative [VOCl 2 (OCH 2 CH 2 OPh)] is monomeric in the solid state.…”
mentioning
confidence: 99%
“…The aryloxyalkoxide derivative [VOCl 2 (OCH 2 CH 2 OPh)] is monomeric in the solid state. Neither ether donor coordination nor alkoxide bridging is found in this complex [11]. In sharp contrast, the alkoxyalkoxide complexes are dimeric and contain a pair of chloride bridging groups instead of alkoxide ones [12].…”
mentioning
confidence: 99%
“…The versatility of these compounds in organic syntheses continues to be explored. As recently reported by the Rosenthal group, vanadium(V)-alkoxide chemistry now shows potential utility in polymer catalysis [91,92]. These studies demonstrated coordination chemistry of mixed vanadium(V) chloro-alkoxides with four-, five-, and six-coordinate vanadium(V) complexes with bridging chloro groups [92].…”
Section: © 2005 Iupac Pure and Applied Chemistry 77 1497-1527mentioning
confidence: 81%
“…The Rosenthal group [91,92] has recently reported an interesting example of this type of chemistry. The mixed vanadium(V) chloroalkoxides investigated are of interest for their application as catalysts, and their coordination chemistry is showing a wide range of geometries with four-, five-, and six-coordinate vanadium(V) in mono and dinuclear complexes with bridged chloro groups [91,92]. As more structures with bridging chlorides such as shown in 7, and their reactivity become available, a better understanding of the structural preferences in these systems will be forthcoming.…”
Section: Fifteen Years Of Dancing With Vanadiummentioning
confidence: 99%
See 1 more Smart Citation